Features of the psychophysical condition of university cadets undergoing police training - Velykyi , Yu.; Kosheleva , O.; Mykytchyk , O.; Moskalenko , D. (Sportyvnyi Visnyk Prydniprovia, 2025)
Introduction. The results of contemporary scientific research indicate that currently there is an insuficient level of psychophysical readiness among university cadets undergoing police training, with a tendency for their physical condition to decline in the senior years. This situation requires systematic monitoring of the psychophysical condition indicators of students throughout their education to timely identify existing problems and determine ways to address them. The purpose of the study is to investigate the indicators of the psychophysical condition of university cadets undergoing police training, in order to identify ways to improve the effectiveness of psychophysical preparation of future law enforcement oficers. Materials and methods of research: analysis of literature sources, pedagogical observation, anthropometric research methods, methods for determining functional state, Tapping Test, Munsterberger Test, methods of mathematical statistics. The results obtained during the study indicate that the anthropometric parameters of the physical development of cadets corresponded to age norms. In the indicators of the functional state of the cardiovascular system of the students, a slight increase in resting heart rate was observed. The results of functional tests with breath-holding were within the age norms. The assessment of physical performance using the Rufier test showed that 63.2% of girls and 56.6% of boys had results at low and below-average levels. The study of physical fitness revealed a low level of development of speed qualities, endurance, and coordination abilities among cadets. The assessment of the state of the nervous system of students using the «Tapping Test» demonstrated that its results did not meet normative requirements. The study of attention development using the Munsterberg test confirmed the predominance of low attention levels in most cadets, along with signs of early fatigue and a high number of errors. Conclusions. The obtained results indicate the need to seek ways to improve the psychophysical training of future police oficers, as well as to implement measures to enhance the development of professionally significant physical and mental qualities of cadets throughout their studies.